Pelaksanaan dan Pengelolaan Pelayanan Bimbingan dan Konseling di SD/MI Serta Perspektif Bimbingan Konseling dalam Pendidikan - Sella Mutiara; Miranti; Yusti Asmeri; Oci Mulia Sari; Zubaidah (JPT : Jurnal Pendidikan Tematik, 2025)
Elementary School/Islamic Elementary School (SD/MI) is one of the formal education levels organized in order to prepare students as future members of society who will fill and continue the ideals of the nation's struggle and prepare them to continue their education to a higher level (secondary school). Guidance teachers as the main implementers of Guidance and Counseling activities in SD/MI in this case handled by class teachers must understand clear expectations and performance and understand the characteristics of the students they face, because the existence of Guidance and Counseling is an integral part of all educational activities in an effort to achieve national education goals. Management of guidance and counseling services is part of the follow-up of the implementation of guidance and counseling both at the elementary education level (SD/MI) and secondary education level (SMP/MTs, SMA/SMK/MA). Therefore, the management of service implementation is a barometer to measure the achievement of implementation objectives as well as evaluate the extent to which the guidance and counseling program has been implemented by the guidance teacher and can provide follow-up on the next activity steps. Therefore, the management of guidance and counseling services cannot be separated from the support and cooperation through organizations, personnel, implementers, facilities and infrastructure, and supervision.